Australia: A Continent Without Native Powdery Mildews? The First Comprehensive Catalog Indicates Recent Introductions and Multiple Host Range Expansion Events, and Leads to the Re-discovery of Salmonomyces as a New Lineage of the Erysiphales - Kiss, Levente; Vaghefi, Niloofar; Bransgrove, Kaylene; Dearnaley, John D. W.; Takamatsu, Susumu; Tan, Yu Pei; Marston, Craig; Liu, Shu-Yan; Jin, Dan-Ni; Adorada, Dante L.; Bailey, Jordan; Cabrera de Álvarez, Maria Graciela; et al. (Frontiers in Microbiology, 2020)
In contrast to Eurasia and North America, powdery mildews (Ascomycota, Erysiphales) are understudied in Australia. There are over 900 species known globally, with fewer than currently 60 recorded from Australia. Some of the Australian records are doubtful as the identifications were presumptive, being based on host plant-pathogen lists from overseas. The goal of this study was to provide the first comprehensive catalogue of all powdery mildew species present in Australia. The project resulted in (i) an up-to-date list of all the taxa that have been identified in Australia based on published DNA barcode sequences prior to this study; (ii) the precise identification of 117 specimens freshly collected from across the country; and (iii) the precise identification of 30 herbarium specimens collected between 1975 and 2013. This study confirmed 42 species representing 10 genera, including two genera and 12 species recorded for the first time in Australia. In Eurasia and North America, the number of powdery mildew species is much higher. Phylogenetic analyses of powdery mildews collected from Acalypha spp. resulted in the transfer of Erysiphe acalyphae to Salmonomyces, a resurrected genus. Salmonomyces acalyphae comb. nov. represents a newly discovered lineage of the Erysiphales. Another taxonomic change is the transfer of Oidium ixodiae to Golovinomyces. Powdery mildew infections have been confirmed on 13 native Australian plant species in the genera Acacia, Acalypha, Cephalotus, Convolvulus, Eucalyptus, Hardenbergia, Ixodia, Jagera, Senecio, and Trema. Most of the causal agents were polyphagous species that infect many other host plants both overseas and in Australia. All powdery mildews infecting native plants in Australia were phylogenetically closely related to species known overseas. The data indicate that Australia is a continent without native powdery mildews, and most, if not all, species have been introduced since the European colonization of the continent.